The cAMP Pathway as Therapeutic Target in Autoimmune and Inflammatory Diseases - Raker, Verena Katharina; Becker, Christian; Steinbrink, Kerstin (Frontiers in Immunology, 2016)
Nucleotide signaling molecules contribute to the regulation of cellular pathways. In the immune system cAMP is well established as a potent regulator of innate and adaptive immune cell functions. Therapeutic strategies to interrupt or enhance cAMP generation or effects have immunoregulatory potential in autoimmune and inflammatory disorders. Here, we provide an overview of the cyclic AMP axis and its role as a regulator of immune functions and discuss the clinical and translational relevance of interventions with these processes.